The Journey towards Inclusion: Exploring the Response of Teachers to the Challenge of Diversity in Schools - Cecilia María Azorín-Abellán (Universidad Pedagógica Nacional, 2018)
The general objective of the research presented in this article was to explore the attention to the diversity of students in kindergartens, and primary and high schools in the Region of Murcia (southeast of Spain). This study adopted a methodology of a quantitative nature. The instrument used to collect the data was the Themis Inclusion Tool (Azorín and Ainscow, 2018), which is a Likert scale aimed at teachers formed by three dimensions: contexts, resources and processes. Themis was administered to 545 teachers from 38 schools. This allowed knowing a series of strengths and weaknesses and diagnosing the profile of the schools (barely inclusive, towards inclusion and inclusive), and verifying statistically significant differences according to the variables studied (type of school, location and school stage). According to the results, the strengths focused on the process dimension, making reference to the teaching work, while the weaknesses were found in the contexts dimension, highlighting the scarce commitment between the schools and their communities. Differences were also found according to the type of school and the school stage. Finally, the predominant profile was "towards inclusion". Therefore, the conclusions pointed to the need to continue working for the development of more inclusive practices in schools.